Events shape long-term memory for story information. Issue 2 (7th February 2023) - Smith, Maverick E.; Kurby, Christopher A.; Bailey, Heather R.
ABSTRACT: We segment what we read into meaningful events, each separated by a discrete boundary. How does event segmentation during encoding relate to the structure of story information in long-term memory? To evaluate this question, participants read stories of fictional historical events and then engaged in a postreading verb arrangement task. In this task, participants saw verbs from each of the events placed randomly on a computer screen and then arranged the verbs into groups onscreen based on their understanding of the story. Participants who successfully comprehended the story placed verbs from the same event closer to each other than verbs from different events, even after controlling for orthographic, text-based, semantic, and situational overlap between verbs. Thus, how people structure story information into separate events during online comprehension is associated with how that information is stored in memory. Specifically, story information within an event is bound together in memory more so than information between events.